CAD-assisted modeling of high dielectric contrast composite materials. Issue 4 (April 2017) - Wiens, Alex; Kohler, Christian; Hansli, Matthias; Schuessler, Martin; Jost, Matthias; Maune, Holger; Binder, Joachim R.; Jakoby, Rolf
Abstract: In this work, a CAD approach to model the effective dielectric properties of binary composite ceramics with high dielectric contrast is presented. Further, composite materials consisting of the tunable ferroelectric material barium strontium titanate (BST) with ɛ f ≈ 2000 ɛ 0 and magnesium borate (MBO) with ɛ d ≈ 7 ɛ 0 were fabricated in 10 volume percent steps. The morphology of the real materials was used to generate a micro granular sample for the CAD model. The material samples were processed to 0.5 mm thick and 8.5 mm wide discs and covered with silver electrodes, forming a parallel-plate capacitor. The dielectric properties of the composites were extracted from the capacitors by means of impedance spectroscopy at 100 MHz. The measured dielectric properties are compared to the proposed numerical model and to a widely used equivalent medium approximation model with regard to effective permittivity, quality factor and tunability.